PENGARUH JUMLAH PENDUDUK DAN TINGKAT PENDIDIKAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) PROVINSI RIAU 2010-2020 - Aswanto Aswanto (PROCEEDING UMSURABAYA, 2022)
One of the important indicators to determine the condition of an area in a certain period is to be able to look at the Gross Regional Domestic Product (GRDP) data both on the basis of current prices and on the basis of constant prices. Population is a human resource that is able to increase output in the economy of a region which in turn will create an increase in Gross Regional Domestic Product (GDP). While education is capital for human resources that can improve abilities both formally and skills, making it easier for human resources to find work because it has a high competitiveness value and results in productivity in work which will produce output of goods and services and ultimately be able to increase the Gross Regional Domestic Product (GDP) of Riau Province. This study aims to examine the effect of population and education level on Gross Regional Domestic Product (GRDP) in Riau Province 2010-2020. This study was analyzed using descriptive statistical analysis and multiple regression analysis using the Eviews 10 application. The results of this study found that the population had a positive and significant effect on the GRDP of Riau Province 2010-2020. While the level of education has a negative and insignificant effect on the GRDP of Riau Province 2010-2020.